Evaluation of sprints performed in futsal: proposal of a training protocol - Soares, Ben Hur (2023)
Futsal is a sport with intermittent characteristics and varied intensities. Objectives: Evaluate the sprints performed by futsal athletes in each tactical position and propose a training protocol. Materials and Methods: This is a quantitative, descriptive and longitudinal study. Environment: Field study. Participants: Carried out with twenty adult futsal athletes, all Brazilians who played in the 2018 and 2019 seasons, being six fixed, eight flanks, and six pivots. The data collect took place through observation of the footage taken in 20 games. It was counting the passes in sprints by position. Data were analysed for a significance level of p ≤ 0.05. The research was approved by the Research Ethics Committee, protocol number 4,078,830. Results: The frequency of sprints per minute was 1.4, with a mean distance of 8.0 ± 3.4 m and occurrence of 30.1 ± 5.6 sprints per game. The results did not show statistically significant differences between the evaluated positions. Conclusion: However, these indicators served as parameters for proposing a training protocol specifically for sprints in the futsal modality, with a distance of less than 34.5m, with 40-second intervals between stimuli, and with a summed distance of at most of 463m.